Does Health System Responsiveness Differ between Insured and Uninsured Outpatients in Primary Health Care Facilities in Asagirt District, Ethiopia? A Cross-Sectional Study - Wubshet Debebe Negash; Asmamaw Atnafu; Desale Bihonegn Asmamaw; Chalie Tadie Tsehay (Advances in Public Health)
Background. An effective designation of health facilities improves the facility’s ability to respond to patients’ legitimate expectations. Limited evidence exists regarding the association between health system responsiveness and financial fairness in Sub-Saharan Africa, particularly in Ethiopia. The purpose of the study was, therefore to evaluate the health system responsiveness among insured and uninsured outpatients in primary healthcare facilities and determine the association between health insurance and health system responsiveness among outpatients. Methods. A facility-based cross-sectional study was conducted between March 30 and April 30,2021. The study sampled 423 participants using a systematic random sampling technique, and the data was collected with structured and pretested questionnaires administered by interviewers. Responsiveness was measured using the short version of the World Health Organization’s multicountry responsiveness survey, which has seven dimensions including autonomy, communication, confidentiality, attention, dignity, choice, and amenities. Using quantile regression, a specific association between health insurance and the health system responsiveness index was examined, adjusting for sociodemographic, quality, and satisfaction-related factors. Results. Of a total of 417 outpatients, 70.74% had health insurance. There was no statistical difference in health system responsiveness among insured and uninsured outpatients. Possession of health insurance was not associated with responsiveness (−0.67; 95%CI: −1.59, 0.25). There was a statistically significant negative relationship between age and responsiveness (−1.33; 95% CI: −2.47, −0.19) among 30–39 year olds and (−1.66; 95% CI: −3.02, −0.32) among 40–49 year olds. However, there was a positive statistical association between responsiveness with urban residence (+1.33; 95%CI: 0.37, 2.29), perceived quality of healthcare (+2.96; 95%CI: 1.95, 4.05), and patient satisfaction (3; 95%CI: 1.94, 4.07). Conclusions. There was no difference in the responsiveness of the health system between insured and uninsured outpatients. All domains need further improvement, particularly those more closely related to patients’ concerns, such as waiting time to get service and choices of healthcare providers. Furthermore, health facility administrators and the government should enhance responsive healthcare services in parallel with quality improvement and patient satisfaction, based on feedback from service users for better performance.